CIRI-CIRI DAN IMPLIKASI SYARIAT: SUATU SOROTAN UMUM - Yaacob, Abdul Monir (Jurnal Syariah, 2019)
Thus is a perception that shariah law is rigid and static and therefore could not meet the needs of modern time and changing situation. Therefore. the article will discuss not in detail. The concept and principles that make shariah law flexible and accommodative and suitable lo all time and situation and above all to all people. The article also deals with the main characteristic of shariah law and secular law. The scope and jurisdiction of both laws describing the objective of makasid of the shariah including the meaning of daruriyyat or necessity, hajiyyat or needs and tahsiniyyat. The role of ijtihad in developing Islamic jurispundence.